2017
DOI: 10.1177/0263774x16680109
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the procurement performance of local governments: A duration analysis of public works

Abstract: Public works often suffer from long durations and time escalations, which entail the dissatisfaction of collective needs. Using micro-level data on the works recently procured by the municipalities of a large Italian region, we analyse delay incurrence and the subsequent time-to-completion of works. For this purpose, we rely on a split-population duration model. Our findings show that appropriate levels of expertise and experience – which are often believed to be lacking in municipalities – have a role in spee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…There are a couple of points worth making from the numbers shown. The first point is that the random sample aligns rather well with national datasets regarding the relatively small share of contracts made by ministries and other central government units (Gori et al 2017). Most of the procurement contracts are made by public units operating at regional and local levels.…”
Section: Contractual Characteristicsmentioning
confidence: 70%
“…There are a couple of points worth making from the numbers shown. The first point is that the random sample aligns rather well with national datasets regarding the relatively small share of contracts made by ministries and other central government units (Gori et al 2017). Most of the procurement contracts are made by public units operating at regional and local levels.…”
Section: Contractual Characteristicsmentioning
confidence: 70%
“…They report empirical research leading to the conclusion that projects promoted by local authorities took longer to complete than works commissioned by the country's central government. Along the same lines, when Gori et al [4] analyzed a dataset concerning public works in Tuscany (central Italy) for local authorities, they found that "insufficient procurement experience is associated with a higher probability of incurring delays and longer work durations" (p. 822). Public works require a level of specialization that not all local authorities possess [38].…”
Section: Time Overrun In the Scientific Literaturementioning
confidence: 98%
“…According to the Agency for Territorial Cohesion (Agenzia per la Coesione Territoriale) [40], the average time to assign works worth less than €1 million is about 5 months, so the Veneto Region seems to perform poorly compared with the national average, despite the public authority managing the procedure being reasonably well organized [44]. We used "population" as a proxy of the dimension of the public authority awarding the contract, assuming that it would be more structured and specialized, the larger the population it serves [4,37]. This may indicate the skills available for managing the contract awarding process and consequently of the time needed to complete the procedure.…”
Section: Category Of Work Number Of Projects Relative Frequency (%)mentioning
confidence: 99%
See 1 more Smart Citation
“…While there is great potential in legislation that adjusts expectations to consider larger issues, there may be a lack of enforcement of these provisions; this can undermine achievement of performance expectations (Vluggen et al 2019). Centralization may be a way forward for consistency, but this may challenge accountability at the level of local government (Gori et al 2017).…”
Section: Challenges For Accountability In Public Procurementmentioning
confidence: 99%